Optimization of transmission conditions for thin interphases in composite materials based on colonial competitive algorithm - Mozafari, H. (Trans Tech Publications, 2011)
In this paper a novel evolutionary universal search strategy called colonial competitive algorithm (CCA) is applied to establish an optimal imperfect transmission condition for a thin epoxy intermediate interphase layer which is bonded between two dissimilar strips of materials. The recently introduced CCA has demonstrated excellent capabilities such as faster convergence and better global optimum achievement. Finally the results of CCA are compared with finite element method (FEM) and genetic algorithm (GA). In application, compression shows the success of CCA for design of adhesive joints in the composite materials.